Cross-Cultural Differences and Similarities in Human Value Instantiation - Hanel, Paul H. P.; Maio, Gregory R.; Soares, Ana K. S.; Vione, Katia C.; de Holanda Coelho, Gabriel L.; Gouveia, Valdiney V.; Patil, Appasaheb C.; Kamble, Shanmukh V.; Manstead, Antony S. R. (Frontiers in Psychology, 2018)
Previous research found that the within-country variability of human values (e.g., equality, helpfulness) clearly outweighs between-country variability. Across three countries (Brazil, India, and the UK), the present research tested in student samples whether between-nation differences reside more in the behaviors used to concretely instantiate (i.e., exemplify or understand) values than in their importance as abstract ideals. In Study 1 (N = 630), we found several meaningful between-country differences in the behaviors that were used to concretely instantiate values, alongside high within-country variability. In Study 2 (N = 677), we found that participants were able to match instantiations back to the values from which they were derived, even if the behavior instantiations were spontaneously produced only by participants from another country or were created by us. Together, these results support the hypothesis that people in different nations can differ in the behaviors that are seen as typical as instantiations of values, while holding similar ideas about the abstract meaning of the values and their importance.